Technical studies about the prestressed insulation cylinder of HL-3 tokamak's center-post - Yin Qiu; Ming Li; Xiaolong Liu; Qinghua Ren; Tao Lin; Jian Liu (Nuclear Engineering and Technology)
The TF coil of HL-3 consists of 20 D-shaped demountable bundles, and all their L-shaped center sections are bonded together as the center-post. To increase its overall rigidity to resist torsional loads and avoid de-bonding failure, the center-post is wrapped by an insulation cylinder with enough prestress. Additionally, the insulation cylinder needs to be of good dimensional precision because the CS coil is winded around it. This paper describes the results of the technical studies carried out during the development of the insulation cylinder, including material selection, parameter calculation, enlacing tests and curing tests.